The circuits and filters handbook. - Chen, Wai-Kai, 1936- (CRC Press, 2009)
This volume, drawn from the Circuits and Filters Handbook, focuses on mathematics basics; circuit elements, devices, and their models; and linear circuit analysis. It examines Laplace transformation, Fourier methods for signal analysis and processing, z-transform, and wavelet transforms. It also explores network laws and theorems, terminal and port representation, analysis in the frequency domain, and more.